In Vitro α-Amylase, α-Glucosidase Inhibition, and Anti-Oxidant Activities of Plant Components in Ya-Hom Teppajid - Chaiyawathanananthn, Pannawat; Duangsri, Wantana; Itharat, Arunporn; Pipatrattanaseree, Weerachai; Ooraikul, Buncha (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Diabetes is characterized by high blood sugar levels or hyperglycemia causing the increase of free radicals which increase the risk of various diseases. Ya-Hom Teppajid which consists of 45 plants and their properties had shown anti-diabetic activities in some herbs and the rest of the herbs have not been studied for these activities. Methods: The ethanolic extract of plant componentsinYa-Hom Teppajid were to investigate α-amylase, α-glucosidase inhibitory, and antioxidant activities (DPPH, and TBARS), including total phenolic (TPC) and total flavonoid (TFC). Results: Twenty-four plants showed antioxidant activities, while fifteen plants exhibited enzyme inhibition of diabetes mechanisms. The ethanolic extract of N. lotus had stronger enzyme inhibitory activities and antioxidant activities than other plant components, although less than the positive standard. Conclusions: Our result can support the efficacy of Ya-Hom-Teppajid for a diabetic. Interestingly, the whole flower of N. lotus was suggested as a better part due to its stronger antioxidant activity by free radicals scavenging property. These herbs can be consumed as food ingredients or food supplements and their consumption should be beneficial to diabetic patients.